Pengaruh Zakat, Inflasi dan UMKM terhadap Pertumbuhan Ekonomi di Indonesia - Atik Andhayani; Hamka; Rosdaniah; Ika Agustina; Farah Juniati Meutianingrum (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Economic growth describes an increase in the standard of living as measured by real output per person. Economic growth is often associated with the process of increasing the production capacity of an economy which is manifested in the form of an increase in national income. In this study, this study uses a quantitative research type. Quantitative research is conducted by analyzing numbers that are measured and calculated using mathematical or statistical tools. Data in the form of numbers will be processed using mathematical or statistical tools to obtain information behind the numbers. The data used in this study were obtained from statistical reports from BPS, BAZNAS and the Ministry of Cooperatives and SMEs on the official websites of each institution. The results of this study found that zakat and MSMEs have an effect on economic growth in Indonesia, while inflation has no effect in this study.